The Ckd. Qld fabRy Epidemiology (aCQuiRE) study protocol: identifying the prevalence of Fabry disease amongst patients with kidney disease in Queensland, Australia - Mallett, Andrew (BMC Nephrol, 2020)
BACKGROUND: Fabry disease (FD) is a rare, lysosomal storage disorder caused by the absence or deficiency of the enzyme alpha-galactosidase A (α-Gal A) that leads to the abnormal accumulation of the lipid globotriaosylceramide (GB3) in a variety of cell types and tissues throughout the body. FD has an x-linked inheritance pattern. Previously thought to be only carriers, females can also experience FD symptomatology. Symptoms vary in type and severity from patient to patient and tend to increase in severity with age. FD symptoms are non-specific and may be shared with those of other diseases. Misdiagnoses and diagnostic delays are common, often resulting in progressive, irreversible tissue damage. The estimated prevalence of FD in the general population is 1:40,000 to 1:117,000 individuals. However, it is estimated that the prevalence of FD in the dialysis population is 0.12 to 0.7%. Little is known about the prevalence of FD in the broader Chronic Kidney Disease (CKD) population. METHODS: This is an epidemiological study of the prevalence of FD in CKD patents identified from the public renal speciality practices in Queensland, Australia. A cascade approach to screening is being employed with dried blood spot testing for blood levels of alpha-galactosidase A (Alpha-Gal), with follow-up testing for patients with abnormal results by plasma levels of globotriaosylsphingosine (Lyso-GB3) for females and non-definitive cases in males. A diagnosis of FD is confirmed through genetic testing of the GLA gene in cases suspected of having FD based upon Alpha-Gal and Lyso-GB3 testing. DISCUSSION: Expected outcomes of this study include more information about the prevalence of FD at all stages of CKD, including for both males and females. The study may also provide information about common characteristics of FD to assist with diagnosis and optimal management/treatment. Screening is also available for family members of diagnosed patients, with potential for early diagnosis of FD and intervention for those individuals. TRIAL REGISTRATION: Queensland Health Database of Research Activity (DORA, https://dora.health.qld.gov.au) pj09946 (Registered 3rd July 2017).